Arborização urbana de acompanhamento viário em Catalão (GO) - Rodrigues, Juliana Paula da Silva (2021)
Urban afforestation provides multiple benefits that cover environmental, aesthetic, economic, and psychosocial aspects. In order to maximize these benefits, the qualitative and quantitative inventories of urban trees are important tools for providing information about the need for pruning, phytosanitary treatments, or removal and planting, as well as for defining priorities for interventions. Therefore, the present research aims to evaluate the urban afforestation of Catalão (GO), through the analysis of master plans and afforestation of the city and construction of a quantitative and qualitative inventory of urban afforestation, in order to provide a better urban socio-environmental quality in this space. for this purpose, we used the methodology of conducting a qualitative and quantitative inventory of forestation, of the type registration, which in addition to listing all the trees, obtaining registration data of each individual tree in the neighborhoods: Evelina Nour I and II, Margon I and Central Area of Catalão. The significant amount of conflicts with the afforestation, the presence of inappropriate species, the need for pruning, both for cleaning and emergency pruning, among other social aspects, show that the quality of the afforestation of the public streets of Catalão needs to be monitored and adapted to more efficient technical standards of maintenance, according to what the related legislation recommends.